Torégira: performance ritual em um quilombo-indígena - Serradela, Larissa Isidoro (2016)
The focus of the dissertation is the ritual context called torégira, carried out by the "quilombo-indígena" people known as Tiririca dos Crioulos, located in the municipality of Carnaubeira da Penha, state of Pernambuco. The objective was to understand the dynamics of care between different materials (Ingold, 2012) and the process of ethnic assertion that resonate from this ritual. The torégira at times approaches and at other times separates from aspects of the Afroindigenous Catholic universe, depending on the relationships drawn by the leaders, as well as enabling potential experiences and behaviors between people, plants and entities. Historically it has been adapted to the social situations and the material flows of this locality, generating well-being and ability to confront some problems in life. The torégira expresses the establishment of the ethnic identity of these people, who have in their history experiences of stigma associated with negative attributes, which now are given new meaning through the articulation of their identities, involvement in public policies linked to territorial demarcation and safeguarding of cultural heritage. This ethnography also reveals the transformation of research methods and who performs them, expressing art and anthropology through interethnic relations using artistic interactions and the organization of data through the use of images produced by the interlocutors themselves and other investigators. Artistic interactions that amplify ethnographic narratives, the possibilities of relations with the field and the expressions of identities.